Hypertension After Multiple Transfusions - S. Untario; R. H. T. Netty; B. Permono (Indonesian Pediatric Society, 1982)
Two patients are reported who developed hypertension with or without convulsions after receiving multiple blood transfusions. The pathogenesis of this complication of transfusion is briefly discussed.